(untitled) (Research, Society and Development, 2021)
This article aims to document a didactic-pedagogical activity carried out by students in a Master’s in Professional and Technological Education class at the Federal Institute of Santa Catarina. The class divided into groups produced fanzines, representing a deep reflection on the contents studied during the semester in the discipline of Conceptual Bases for Professional and Technological Education, taught by Professor Dr Adriano Larentes da Silva. The fanzine produced by the group was made with clippings from magazines and newspapers and dealt with themes related to the structural duality in education, the influence of multilateral organizations on educational policies, the conflicts between capital and work and the reform of secondary education. Each section of the article brings a photo of a page from the fanzine produced and the theoretical framework that supported such reflections.